Effects of intermittent-endurance fitness on match performance in young male soccer players - Castagna, C.; Impellizzeri, F.; Cecchini, E.; Rampinini, E.; Alvarez, J. C. B. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to examine the effect of specific endurance (Yo-Yo Intermittent recovery test level 1, Yo-Yo IR1) on match performance in male youth soccer. Twenty-one young, male soccer players (age 14.1 ± 0.2 years) were involved in the study. Players were observed during international championship games of corresponding age categories and completed the Yo-Yo IR1 on a separate occasion. Physical (distance coverage) and physiological match demands were assessed using Global Positioning System technology and heart rate (HR) short-range telemetry, respectively. During the match (two 30-minutes halves), players covered 6,204 ± 731 m, of which 985 ± 362 m (16%) were performed at high intensities (speed >13 km·h-1, HIA). A significant decrement (3.8%, p = 0.003) in match coverage was evident during the second half. No significant (p = 0.07) difference between halves was observed for HIA (p = 0.56) and sprint (speed >18 km·h-1, SPR) distances. During the first and second halves, players attained the 86 ± 5.5 and 85 ± 6.0% of HRmax (p = 0.17), respectively. Peak HR during the first and second halves were 100 ± 4 and 99.4 ± 4.7% of HRmax, respectively. Yo-Yo IR1 performance (842 ± 352 m) was significantly related to match HIA (r = 0.77, p < 0.001) and total distance (r = 0.65, p = 0.002). This study's results showed that specific endurance, as determined by Yo-Yo IR1 performance, positively affects physical match performance in male young soccer players. Consequently, the Yo-Yo IR1 test may be regarded as a valid test to assess game readiness and guide training prescription in male youth soccer players.